More Than 500 Kids Could Be Saved Each Year! Ten Consensus Actions to Improve Quality of Pediatric Resuscitation in DACH-Countries (Austria, Germany, and Switzerland) - Philipp Jung; Sebastian Brenner; Iris Bachmann; Christian Both; Francesco Cardona; Christian Dohna-Schwake; Christoph Eich; Frank Eifinger; Ralf Huth; Ellen Heimberg; Bernd Landsleitner; Martin Olivieri; et al. (Frontiers Media S.A., 2020)
• Quality and outcome of pediatric resuscitation often does not achieve recommended goals.• Quality improvement initiatives with the aim of better survival rates and decreased morbidity of resuscitated children are urgently needed.• These initiatives should include an action framework for a comprehensive, fundamental, and interprofessional reorientation of clinical and organizational structures concerning resuscitation and post-resuscitation care of children.• The authors of this DACH position statement suggest the implementation of 10 evidence-based actions (for out-of-hospital and in-house cardiac arrests) that should improve survival rates and decrease morbidity of resuscitated children with better neurological outcome and quality of life.